Decoding Time of Death: Histopathological Dynamics of Intervertebral Discs as a Novel Marker for Postmortem Interval Estimation - Selcuk Cetin; Tugba Ataseven; Ilkay Kalkanli; Bulent Eren (Diagnostics)
Objectives: Determination of the postmortem interval (PMI) remains a critical challenge in forensic science. Intervertebral discs, due to their structural resilience, hold promise as a reliable tissue for PMI estimation; however, studies focusing on their forensic applicability remain limited. This study aimed to evaluate progressive histopathological changes in intervertebral discs at specific postmortem intervals and assess their forensic applicability. Materials and Methods: A total of 48 rats were divided into six groups: control (0 h), 7-day, 15-day, 30-day, 60-day, and 90-day postmortem intervals. Intervertebral disc samples were stained with hematoxylin–eosin and trichrome, and histopathological parameters such as homogenization, eosinophilia, dissociation, nuclear alterations (pyknosis and karyolysis), and collagen fragmentation were analyzed. Results: Statistically significant changes were observed across postmortem intervals (p < 0.001). Homogenization progressed from mild changes at 7 days to prominent levels by 90 days. Eosinophilia and dissociation between the epithelium and connective tissue also increased significantly over time (p < 0.001). Collagen fragmentation, initially minimal, became severe at the 90-day interval. The observed changes demonstrated a clear, time-dependent progression strongly correlating with the PMI. Conclusions: Our findings suggest that histopathological changes in intervertebral discs follow a consistent and time-dependent pattern, making them a potential forensic marker for PMI estimation. This has important implications for forensic science, as it offers an alternative tissue type that is less susceptible to early decomposition compared to soft tissues. These results suggest that the intervertebral disc is a promising tissue for PMI estimation, offering a complementary approach to existing forensic methods.